The Jagged edge of duty : a fighter pilot's world war II - Richardson, Robert L. (Guilford, Connecticut : Stackpole Books, 2017)
The World War II fighter-pilot story. On the very first day of the invasion of Sicily, three months into his combat career, Allan Knepper flew his P-38 Lightning fighter in a squadron sent out to sweep the island and interdict German ground targets. Retreating German infantry unexpectedly pounded the American flyers. Knepper was one of two shot down; he was never found. Knepper's story is the story-in-microcosm of thousands of American fighter pilots in World War II. Richardson recounts Knepper's experiences from training through combat and uses them to discuss the aircraft, tactics and doctrine, training, base life, and aerial combat of the war. This is the intimate account of one pilot at war, but also the anatomy of the fighter-pilot experience in World War II.
CHAPTER 1. GUMP -- 2. Squadron organization -- 3. Two flyers for the fray -- 4. America with no choice left -- 5. Meet the group -- 6. Meet the pilots -- 7. Bomber escort -- 8. Losses mount and the mission to Palermo -- 9. The P-38 fighter interceptor 10. Attacks on Sardinia -- 11. When things go wrong -- 12. Bombs at their fingertips -- Approaching air rule -- Aftermath -- The search for Allan Knepper -- After combat -- Epilogue.
Includes index.
Keywords: FIGHTER PILOTS -- UNITED STATES -- BIOGRAPHY